Inter-allelic recombination in the Plasmodium vivax merozoite surface protein 1 gene among Indian and Colombian isolates (2004)
ABSTARCT: A major concern in malaria vaccine development is the polymorphism observed among different Plasmodium isolates in different geographical areas across the globe. The merozoite surface protein 1 (MSP-1) is a leading vaccine candidate antigen against asexual blood stages of malaria parasite. To date, little is known about the extent of sequence variation in the Plasmodium vivax MSP-1 gene (Pvmsp-1) among Indian isolates. Since P. vivax accounts for >50% of malaria cases in India and in Colombia, it is essential to know the Pvmsp-1 gene variability in these two countries to sustain it as a vaccine candidate. The extent of polymorphism in Pvmsp-1 gene among Indian and Colombian isolates is described. Methods: The sequence variation in the region encompassing the inter-species conserved blocks (ICBs) five and six of Pvmsp-1 gene was examined. PCR was carried out to amplify the polymorphic region of Pvmsp-1 and the PCR products from twenty (nine Indian and 11 Colombian) isolates were sequenced and aligned with Belem and Salvador-1 sequences. Results: Results revealed three distinct types of sequences among these isolates, namely, Salvador-like, Belem-like and a third type sequence which was generated due to interallelic recombination between Salvador-like sequences and Belem-like sequences. Existence of the third type in majority (44%) showed that allelic recombinations play an important role in PvMSP1 diversity in natural parasite population. Micro-heterogeneity was also seen in a few of these isolates due to nucleotide substitutions, insertions as well as deletions. Conclusions: Intergenic recombination in the Pvmsp-1 gene was found and suggest that this is the main cause for genetic diversity of the Pvmsp-1 gene.